FUNCTIONS OF THE VILLAGE DELIBERATIVE BODY IN SUPERVISION OF VILLAGE GOVERNMENT BASED ON VILLAGE LAWS AND REGULATIONS AND ISLAMIC LAW - Dedi Ramades; Mohammad Akbar Husni (Journal of Islamic and Interdisciplinary Research, 2025)
This research aims to: 1) identify and analyze the regulations of the Village Consultative Body in carrying out government supervision. village ; 2) knowing and analyzing the function of the Village Consultative Body in supervising government village . Research method. This research is a normative legal research and the approaches used are the legislative approach , conceptual approach and historical approach. The results of the research show that (1) The regulation of the Village Consultative Body in carrying out government supervision village . The Village Representative Body (BPD) in Law Number 22 of 1999 is a village legislative body that functions to protect customs, in the Minister of Home Affairs Decree No. 64 of 1999 concerning General Guidelines for Village Regulations . The new Law on Regional Government, namely Law No. 32 of 2004 as a replacement for Law No. 22 of 1999, regulates the existence of the Village Representative Body (BPD) which has changed its name to the Village Consultative Body (BPD). (2) The Function of the Village Consultative Body in the Implementation of Village Government According to Village Government Regulations. Law Number 6 of 2014 explains that the function and role of the Village Consultative Body as stipulated in Law Number 32 of 2004 is weakened by limiting it to legislation and representation. Its role, function and position are further narrowed in Law Number 6 of 2014 concerning Villages, the legislative function of the BPD is limited. The alignment between legal regulations and Sharia principles demonstrates that Islam makes a significant contribution to the development of village governance. Effective oversight can prevent irregularities and promote just and transparent governance. By implementing the values ​​of trust, shura, and amar ma'ruf nahi munkar, the BPD can become a dignified oversight institution.